SARS-CoV-2 contact tracing among disadvantaged populations during epidemic intervals should be a priority strategy: results from a pilot experiment in Barcelona. (June 2021) - Vallès, X.; Roure, S.; Valerio, L.; López-Muñoz, I.; Pérez-Quílez, O.; Soldevila, L.; Martín-Cano, L.; Estrada, O.; Palacín, M.D.; Blanco, I.; Orozco, J.; Esquerrà, A.; et al.
Abstract: Objectives: The aim of this study was to trace contacts of coronavirus disease 2019 (COVID-19) hospitalised patients and determine the risk factors of infection in urban areas. Study design: Longitudinal analysis of contacts identified from index cases. Methods: A contact tracing study was carried out in the Northern Metropolitan area of Barcelona, Spain, during the inter-epidemic lapse of May to July 2020, a period of low SARS-CoV-2 incidence. Index cases were notified from the referral hospital. Contacts were traced and followed up for 14 days. Reverse transcription polymerase chain reaction was performed on day 0 and day 14 for contacts. Results: In total, 368 contacts were identified from 81 index cases (median of seven contacts per index case), from which 308 were traced successfully. The median age of contacts was 28 years, 62% (223 of 368) were men. During the follow-up period, 100 contacts tested positive for COVID-19 (32.5% [95% confidence interval CI = 27.3–38.0]), with a secondary infection rate of 48.3% (95% CI = 40.8–55.9) among housemates. Clusters of index and respective contacts tended to aggregate within disadvantaged neighbourhoods ( P < 0.001), and non-national index cases (N = 28, 34.1%) resulted in higher secondary infection rates compared with nationals (51.0% [95% CI = 41.0–60.9] vs 22.3% [95% CI = 16.8–28.8]; P < 0.001). Conclusions: Disadvantaged communities experience a disproportionate burden of COVID-19 and may act as infection reservoirs. Contact tracing with a cross-cutting approach among these communities is required, especially during inter-epidemic periods.